2021
DOI: 10.6007/ijarbss/v11-i9/11140
|View full text |Cite
|
Sign up to set email alerts
|

Towards Digital Engagement – Exploring Academic Writing Conferencing and Collaborative Writing Using Google Docs

Abstract: Academic writing is a complex process for learners as they are required to transfer their thoughts into writing not only by using correct language but also formatting. When the world was struck by the Covid-19 pandemic, learning is migrated to online platforms. Instructors need to search for the best pedagogy to ensure the process of teaching and learning is not disrupted. Web 2.0 tools is perceived to be an ideal resource to assist instructors in teaching academic writing. Online writing tools like Google Doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The global pandemic underscored the urgency for educators to swiftly adapt to the digital realm, prompting a reassessment of teaching methodologies and the integration of relevant technological tools. As evidenced by Bakar's (2021) study at the defense university, which explored the incorporation of collaborative learning and feedback through digital approaches in the academic writing course, the findings demonstrated a positive reception. This not only highlights the adaptability of students but also emphasizes the importance of an educational environment that embraces technological advancements to optimize learning outcomes.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The global pandemic underscored the urgency for educators to swiftly adapt to the digital realm, prompting a reassessment of teaching methodologies and the integration of relevant technological tools. As evidenced by Bakar's (2021) study at the defense university, which explored the incorporation of collaborative learning and feedback through digital approaches in the academic writing course, the findings demonstrated a positive reception. This not only highlights the adaptability of students but also emphasizes the importance of an educational environment that embraces technological advancements to optimize learning outcomes.…”
Section: Introductionmentioning
confidence: 87%
“…The onset of the global pandemic has hastened the urgency for educators to swiftly adapt to the digital landscape, prompting a reassessment of teaching methodologies and the integration of pertinent technological tools. Bakar's (2021) study conducted at the defense university, which delved into the integration of collaborative learning and feedback through digital means within the academic writing course, unveiled a positive response, highlighting students' adaptability and the pivotal role of embracing technological advancements in education. The current findings align closely with Bakar's (2021) earlier research at the same defense university, wherein educators echoed the importance of fostering a teaching and learning environment tailored to the demands of 21st-century learning, emphasizing learner-centeredness.…”
Section: Students' Learning Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, using Google Docs as a collaborative tool in learning writing is not new as it has started even before the pandemic. Previous studies (Suwantarathip & Wichadee, 2014;Talib & Cheung, 2017;Basri et al, 2019;Yaacob & Yunus, 2019;Sudrajat & Purnawan, 2019;Hidayat, 2020;Bakar, 2021) have shown that the integration of Google Docs in learning writing has positive impacts, benefited the students in their writing, as their writing skill is enhanced, and they are motivated to learn. Google Docs is a web-based application that allows students and teachers to collaborate synchronously and asynchronously by writing, commenting, proofreading, and editing the online text.…”
Section: Introductionmentioning
confidence: 98%